British Rule in India - Sunderlal, Pandit (New Delhi Sage Select, 2018)
"Interested in this nation's political history. In 1929, Pandit Sunderlal's original work in four volumes, Bharat Mein Angrezi Raj, was banned by the British because of its fearless criticism of their rule in India. In sharp contrast to the histories of India written by British historians, who stressed that India was in a state of arrested development before the British arrived, Pandit Sunderlal produced a work that celebrated India's past. In 1960, the Government of India brought out this history in two parts: How India Lost Her Freedom and British Rule in India. The former details how British traders penetrated the sub-continent and established the foundation of their rule. The latter covers the period from 1805 (Second Maratha War), a turning point for the East India Company, to 1858, when the East India Company had to cede control to the British Crown. It details how the British acquired territories by sly and dishonourable treaties and how their rule led to extremely large-scale economic exploitation. It painstakingly traces the history of the deliberate destruction of Indian industry and the plundering that went on under the guise of development."--Provided by publisher.
Include Illustrations and Index
Keywords: British Occupation of India (1765-1947)